The rise and fall of Ava Arcana : a novel - Banash, Jennifer (Lake Union Publishing, 2023)
"An electrifying novel about a woman in thrall to the exhilarating rhythms of Manhattan, lost in the dizzying promise of youth, and fatally naive to the dark pressures of fame. When Rolling Stone journalist Kayla McCray is assigned a cover story on pop icon Lexi Mayhem, Kayla stumbles across a startling new angle to the exposé. Years ago, another rising star from Lexi's past mysteriously leaped to her death. Some things are better off forgotten, Lexi says. Kayla disagrees. It's 2005 and Ava Petrova moves to New York with a notebook full of songs and a dream. Then she meets Lexi, an up-and-coming singer who brands Ava with an enigmatic new stage name and introduces her to an intoxicating city alive with possibilities. From fast friends and kindred spirits to creative muses and inseparable soul mates, Ava and Lexi embark on a parallel journey to stardom, but there is room for only one at the top. As past and present converge, Kayla chases the ghost of a young woman doomed by betrayal and erased by a secret, and unravels the truth that it takes more than ambition to become a star."--Amazon website.